PENDAYAGUNAAN LUMPUR GAMBUT DAN KOTORAN SAPI UNTUK MEMPERCEPAT COMPOSTING PADA SAMPAH RUMAH TANGGA - Ihsan, Bagus Muhammad; Khayan, Khayan; Sucipto, Cecep Dani; Puspita, Widyana Lakshmi; Nasihin, Nasihin (Jurnal Abdi Insani, 2024)
Environmental pollution-based diseases, nationally like ISPA, malnutrition, diarrhea and thypus are still high. These diseases can be transmitted through disposal of local households and farms that are naturally disposed of (traditionally) unhealthy, such as open dumping, irrigation and dumping in wells. (parit). To control parasites such as helminths and their vectors, health technology is needed, especially for the use of domestic garbage and local cattle debris feces for composting. In addition to serving for the fertilization of crops, the production of composting also added economic value to farmers' incomes and improved public health, as well as the reduction of germs and parasite diseases. The production of composting of household garbage and livestock food residues can be accelerated using cabbage mud and cattle feces. The use of crab mud can accelerate such composting processes, because in cabbag mud contains microbiological Bacilus sp. aerobic/ anaerobic cutting agents. Adding cattle dirt to the composting process can be useful in accelerating the biodegradation process of household garbage. This ability is due to microorganisms such as protozoa, function, Streptococcus sp. and cellulolithic bacteria, which produce cellulose that can break down (biodegradate) the whole substance in household garbage. The purpose of dedication to the community is to expect the cadres and the community to use the mud and feces of cattle to make compost fertilizer. Research methods use Observational and Socialization to the variables studied. The result of dedication to this community is increasing knowledge about cabbage and cow dirt to accelerate composting on household garbage as well as obtaining compost fertilizer for the community.